Composition And Structure Vegetation Of Lowang Gali Tourism Forest, East Lombok Regency - Ahmad nawawi nawawi; Firman Ali Rahman; Maya Ekaningtias; Alfian Pujian Hadi; Ahmad Fadli (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2020)
The composition and structure of vegetation is one way to determine the level of control and distribution of a habitat, including in Lowang Gali forest tourism which has the potential as an educational tourism area in East Lombok Regency. Based on the observations, there were 14 families with 22 species of woody plants. The moraceae family is the family with the largest number of species, consisting of 5 (five) ficus genera, namely: Ficus racemosa, Ficus salicifolia, Ficus variegate, Ficus sur and Ficus seftica. Based on the results of data analysis, the highest INP value for seedlings was Ficus seftica (23,39%), the highest sapling was Alstonia scholaris (19,80%), the highest pile strata was Dysoxylium gaudichadianun (50,44%) and tree strata. the highest were Alstonia scholaris (45,15%) and Dysoxylium gaudichadianun (45,15%). The index value of plant species diversity in the Lowang Gali forest tourism area is more than 1 (1 ≤H'≤ 3) which indicates moderate diversity.